Synthesis of research on ENFit gastrostomy tubes with potential implications for US patients using these devices. (14th February 2022) - Guha, Suvajyoti; Herman, Alexander; Antonino, Mark; Silverstein, Joshua S.; Venkataraman‐Rao, Priya; Myers, Matthew R.
Abstract: Misconnections between enteral devices and other medical devices have been associated with patient death and serious injuries. To minimize such misconnections, the design of connectors on enteral devices has been standardized. The most common adaptation of the standardized enteral connector is called ENFit. Gastrostomy tubes (G‐tubes), which may or may not possess the ENFit connector, are increasingly used to deliver commercial and blenderized diets in home settings to enteral device users. To investigate and compare the performance of G‐tubes with and without ENFit connectors, research investigations have recently been performed. However, synthesis of such investigations and quantitative discussion of the consequences of transitioning to ENFit‐based G‐tube devices has not yet occurred. Here we review the research findings from these studies, with data on patient practices from a Mayo Clinic survey, to estimate the impact on tube feeders in home settings of transitioning to ENFit‐based G‐tube devices. Extrapolating the findings from these studies to US enteral G‐tube patients, 1.5%–8.6% of adult patients and 0.2%–1.9% of pediatric patients may experience perceptible slowing in their gravity feeds if using ENFit‐based G‐tube devices. About 2.5%–8.6% of adult patients and 0.5%–5.5% of pediatric patients (or their caregivers) may need to push with perceptibly more force for syringe push‐based feeding using ENFit‐based G‐tube devices. Lastly, the article offers suggestions for patients and device manufacturers. [Correction added on 2 May 2022, after first online publication: In the preceding sentence, the percentage of adult patients was revised from 2.5%‐8.6% to 1.5%‐8.6%.]